Folikulární lymfomy: molekulární diagnostika t(14;18)(q32;q21)--fluorescencní in situ hybridizace, kvalitativní a kvantitativní PCR - Mrhalová, M; Krsková, L; Kalinová, M; Soukup, J; Kodet, R (Ceskoslovenska patologie, 2003)
Diagnosis of follicular lymphoma (FL) is based on histology and immunohistochemical profile (CD20+, CD79alfa+, CD10+, BCL-2+, CD5-). A chromosomal marker--translocation t(14;18)(q32;q21) supporting the tumor diagnosis and useful for monitoring bone marrow or peripheral blood infiltration by the tumor cells is also used. The BCL2 gene (18q21) is controlled by an enhancer of the IGH gene (14q32) resulting in BCL-2 protein overexpression. The translocation is present in the majority of patients with FL. The aim of the study was to introduce the quantitative PCR (RQ-PCR, real-time quantification) method for the assessment of the quantity of cells bearing the translocation t(14;18) in patients with FL. The fluorescence in situ hybridization on interphasic nuclei (I-FISH) in histologic sections was used for screening of patients with the t(14;18). A search for the break of the BCL2 gene at the major breakpoint region (mbr) was performed by means of qualitative PCR. We determined the relative number of the tumor cells bearing t(14;18) translocation (mbr) in patients with FL by the RQ-PCR. The relative quantity of these cells was significantly higher in the lymph nodes than in the bone marrow or peripheral blood. The RQ-PCR is a tool of choice to monitor the activity of the disease in individual patients, and to detect an early disease relapse before its manifestation at the level diagnosed by morphology.
Keywords: geny bcl-2; Genetic Markers; polymerázová řetězová reakce; folikulární lymfom; In Situ Hybridization, Fluorescence; genetické markery; lidé středního věku; lidé; ženské pohlaví; Translocation, Genetic; Immunoglobulin Heavy Chains; Lymphoma, Follicular; Molecular Diagnostic Techniques; diagnostické techniky molekulární; Female; mužské pohlaví; Polymerase Chain Reaction; hybridizace in situ fluorescenční; Middle Aged; translokace genetická; Humans; těžké řetězce imunoglobulinů; Genes, bcl-2; Male